Level and factors of support for the Living with the Virus policy in a Chinese adult general population: a mediation analysis via positive and negative attitudes toward the policy - Lau, Joseph T. F.; Ng, Joyce Hoi-Yuk; Goodwin, Robin; Kang, Tarandeep S.; Fong, Vivian W. I.; Lau, Mason M. C.; Yu, Yanqiu (Frontiers in Public Health, 2024)
Background This study investigated the public’s support for the Living with the Virus (LWV) policy, its associated factors, and related mediations at a time when more countries were considering adopting the LWV policy amid the COVID-19 pandemic. Methods A random, population-based telephone survey was conducted among 500 Chinese adults in Hong Kong during March/April 2022. Results 39.6% of the participants were supportive/strongly supportive of the LWV policy. Perceived efficacy of the control measures was negatively associated with the support and was partially mediated via the perception that the policy would greatly improve the economy/daily life of the policy. Perceived physical harms of the Omicron variant was negatively associated with the support and was fully mediated via perceived negative impacts of the policy. 26.2%/54.6% believed that the policy would improve the economy/daily life greatly; about 40% perceived negative impacts on deaths and the medical system due to the policy. COVID-19 ever infection did not significantly moderate the studied associations. Conclusion The public was split regarding the support for the LWV policy and whether it would cause better economy/daily life, unnecessary deaths, and the collapse of the medical system. Health communication is needed in shifting toward the LWV policy.